Bullying and defending behavior: The role of explicit and implicit moral cognition. (December 2016) - Pozzoli, Tiziana; Gini, Gianluca; Thornberg, Robert
Abstract: Research on bullying has highlighted the role of morality in explaining the different behavior of students during bullying episodes. However, the research has been limited to the analysis of explicit measures of moral characteristics and moral reasoning, whereas implicit measures have yet to be fully considered. To overcome this limitation, this study investigated the association between bullying and defending, on one hand, and both explicit (moral disengagement, self-importance of moral values) and implicit (immediate affect toward moral stimuli [IAMS]) moral components, on the other hand. Young adolescents ( N  = 279, mean age = 11 years, 9 months, 44.4% girls) completed a series of self-report scales and individually performed a computer task investigating the IAMS. Two hierarchical regressions (bootstrapping method) were performed. Results showed that moral disengagement was associated with bullying and defending behavior at high levels of IAMS, however not when IAMS was low. In contrast, self-importance of moral values was not significantly associated to the two behaviors when IAMS was high whereas both associations were significant at low levels of IAMS. These results significantly expand previous knowledge about the role of morality in bullying and defending behavior. In particular, they highlight the role of the interaction between explicit and implicit moral dimensions in predicting bullying and defending behaviors. Highlights: Relations of explicit/implicit morality with bullying and defending are analyzed. Moral disengagement and self-importance of moral values are measured explicitly. Immediate affect toward moral stimuli (IAMS) is measured via a computer task. Moral disengagement is associated with both behaviors only when IAMS is high. Self-importance of moral values is associated with both behaviors only when IAMS is low.